Changes of Functional, Morphological, and Inflammatory Reactions in Spontaneous Peripheral Nerve Reinnervation after Thermal Injury. (1st February 2022) - Yu, Xing; Liu, Chang; Ji, Caihong; Lenahan, Cameron; Fang, Yuanjian; Wang, Yong; Shao, Anwen
Abstract : In recent decades, the use of energy-based devices has substantially increased the incidence of iatrogenic thermal injury to nerves (cauterization, etc.). While recovery of the nerve after thermal injury is important, the changes in neural structure, function, and peripheral inflammatory reactions postinjury remain unclear. This study is aimed at demonstrating the changes mentioned above during the acute, subacute, and chronic stages of nerve reinnervation after thermal injury. Spontaneous reinnervation was evaluated, including the neural structures, nerve conduction abilities, and muscle regeneration. These effects vary depending on the severity of thermal injury (slight, moderate, and severe). Peripheral inflammatory reactions, as impediments to reinnervation, were found in significant numbers 3 days after thermal injury, exhibiting high expression of IL-1 β and TNF- α, but low expression of IL-10. Our findings reveal the pathogenesis of peripheral nerve reinnervation after thermal injury, which will assist in selecting appropriate treatments in further research.